Malaysia's Islamic Educational Policy in Addressing the Challenges of Globalization - Helmiati, Helmiati; Arfan, Surya (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Globalization presents challenges and opportunities for Islamic education. This article aims to examine Malaysia's Islamic education policies in addressing the challenges and opportunities of globalization and analyze them based on experts' perspectives. A literature study with a qualitative approach is used to analyze policy documents and the views of Islamic education experts and researchers. The results show that among Malaysia's education policies to strengthen Islamic education are curriculum reform, integration of science and Islam in the curriculum, emphasis on character education, development of teacher professionalism, integration of information and communication technology in education, improvement of the quality of leadership and school management, development of Islamic higher education. The policies are intended to create a balance between maintaining the identity and practice of Islam and the development of the country according to the demands of globalization. With these strategic steps, the younger generation is expected to compete at the national and international levels with a strong national character without losing fundamental values. The Islamic education policy in Malaysia shows an adaptive effort to the challenges of globalization.